Regulatory Reconstruction of Electoral Process Dispute Resolution Based on Justice In Indonesia - Suriyanti, Lili; Oktavianus, Afriman (Pelopor Publikasi Akademika, 2025)
This study aims to analyze the weaknesses of regulations on election dispute resolution in Indonesia and formulate a more equitable regulatory reconstruction to increase the effectiveness and legal certainty in the election process. Using normative juridical methods and empirical approaches, this study examines the applicable regulations. The results of the study show that the current regulations do not fully reflect the principle of substantive justice, the effectiveness of the electoral dispute resolution system in Indonesia is still constrained by the imbalance between legal structure, legal substance, and legal culture. As a solution, this study recommends the reconstruction of election dispute resolution regulations, including extending the dispute resolution period to 21 working days, strengthening the legal force of mediation results to be binding, ensuring that the execution of adjudication decisions can run well, and applying sanctions for election organizers who do not carry out the decision in a timely manner. The novelty of this study lies in the critical analysis of the weaknesses of nationally applicable regulations as well as the proposed legal reconstruction that emphasizes more on substantive justice in resolving election disputes in Indonesia. With the improvement of regulations, it is hoped that the election dispute resolution system in Indonesia can be more transparent, effective, and fair, thereby increasing public trust in the election process and strengthening the legitimacy of election results in Indonesia.